Penguatan Kapasitas Sumberdaya Manusia Dan Manajemen Kelembagaan Petani Kopi Robusta Temanggung Sebagai Upaya Penguatan Ekonomi Lokal Berbasis Indikasi Geografis - Dwiningtyas Padmaningrum (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Temanggung robusta coffee has flavors and raw material components that reflect the regional characteristics. To assure the quality and increase the competitiveness, coffe harvesting and post-harvest processing must be carried out according to the geographical indication standart (IG). The application standar of IG practically still has several problems such as a low motivation of harvest and post-harvest processing aspects as well as farmer’s group management. By cooperating with two farmers’ group in Muncar and Ngadisepi village, Gemawang sub-district, Temanggung Regency, Universitas Sebelas Maret has implemented community partnership program. This aim at increasing motivations and skills of farmers in managing coffee processing based on IG standart. Methods used in this programs include: (1) training, (2) introduction of a pulper device, and (3) supervision. This program has: (1) increased motivation, knowledge, skills of farmers’ group in coffee post-harvest processing based on IG standart, (2) increased motivation for strengthening management of farmers’ group institutions, (3) provided applied technology, and (4) increased the economic of coffee value added.